2022
DOI: 10.1186/s13613-022-01054-0
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra in pediatric acute fulminant myocarditis

Abstract: Background Acute fulminant myocarditis in children is associated with elevated mortality and morbidity with few advances in its medical management. Here we report a preliminary experience of children treated with IL-1 receptor antagonist associated with rapid myocardial function recovery. Methods A retrospective case series of children admitted in the Pediatric Intensive Care Unit of the Bicêtre Hospital (AP–HP Paris Saclay University) between Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Of interest, the use of biotherapies did not increase over the waves. A French team showed that use of anakinra was associated with a rapid stabilization and recovery in seven patients with acute fulminant myocarditis in an MIS-C setting ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, the use of biotherapies did not increase over the waves. A French team showed that use of anakinra was associated with a rapid stabilization and recovery in seven patients with acute fulminant myocarditis in an MIS-C setting ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several nonconventional forms of immunosuppression have been proposed or are under investigation to determine their potential benefits in the context of AM. These include recombinant cytokine receptor antagonists such as anakinra [73][74][75] or lymphocyte components involved in the inflammatory process in myocarditis. Noncorticosteroid immunosuppressants including AZA, 69,76,77 MTX, 78 and cyclosporine 67 have also been proposed for use in the management of myocarditis.…”
Section: Nonconventional Immunosuppressantsmentioning
confidence: 99%
“…79 Case reports and case series have suggested that anakinra, a recombinant human IL-1 receptor antagonist, may promote LV function recovery in both adults and children with lymphocytic AM. 73,74 More robust evidence on treatment of AM with anakinra comes from the Anakinra versus Placebo for the Treatment of Acute Myocarditis (ARAMIS) trial, which is now completed and has compared anakinra in addition to standard therapy versus standard therapy alone in admitted patients with AM (NCT03018834). 75 Results from the ARAMIS trial showed that Anakinra is safe for use but does not reduce the complications of myocarditis in a relatively low risk population.…”
Section: Anakinra and Other Monoclonal Antibodiesmentioning
confidence: 99%
“…Furthermore, many patients received Remdesivir or Hydroxy-chloroquine [ 33 ]. Finally, Maunier et al emphasised the possible therapeutic value of Anakinra in 7 paediatric cases of COVID-19-associated FM [ 106 ]. An overview of the specific subtypes of FM, the role of MCS, and additional treatment options are depicted in Table 2 .…”
Section: Epidemiology Of Myocarditismentioning
confidence: 99%